2005
DOI: 10.1261/rna.2560905
|View full text |Cite
|
Sign up to set email alerts
|

Evolvability of the mode of peptide binding by an RNA

Abstract: The HIV Rev-response element (RRE) RNA binds strongly to two unrelated peptides, the HIV Rev peptide and an RRE-binding aptamer, the RSG-1.2 peptide, at a similar site, but using distinct sets of interactions. In this study, the nucleotide base requirements for the binding of the RRE to the Rev and RSG-1.2 peptides were determined by selection of Rev- and RSG-1.2-binding RRE variants using a bacterial reporter system. As a result, distinct differences in the bases necessary for binding the two peptides were fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
31
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 40 publications
(87 reference statements)
4
31
0
Order By: Relevance
“…However, experimental evidence with biologically active RNAs has been limited. Experimental support for the application of neutral theories to RNA activity has come from only a few examples (18,22,23,40). Our findings that single substitutions connect a P22 N-specific boxB via a moderately bifunctional boxB to a N-specific boxB support the extension of neutral theories from computationally predictable RNA secondary structures to biologically active RNA phenotypes.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…However, experimental evidence with biologically active RNAs has been limited. Experimental support for the application of neutral theories to RNA activity has come from only a few examples (18,22,23,40). Our findings that single substitutions connect a P22 N-specific boxB via a moderately bifunctional boxB to a N-specific boxB support the extension of neutral theories from computationally predictable RNA secondary structures to biologically active RNA phenotypes.…”
Section: Discussionmentioning
confidence: 53%
“…Though computational modeling of evolving RNA secondary structure strongly supports neutral theories (21,38,45), few experimental tests using biologically active RNAs have been reported. Studies of small hairpin RNAs that bind arginine-rich peptides have shown that single substitutions and base pair changes are enough to create changes of specificity (23,41), suggesting that neutral paths between distinct activities can be found when sequences are small. In the case of protein-binding RNAs, mutations leading from relaxed-specificity sequences to sequences with distinct binding preferences would be equivalent to speciation.…”
mentioning
confidence: 99%
“…The reciprocal mechanism of adopting both P22 and boxB loop conformations appears to be employed by relaxed-specificity boxBs (11). Relaxedspecificity sequences may be able to acquire specificity simply by mutations that discriminate against one target without affecting binding to another, as has been seen in HIV RRE (26).…”
Section: Discussionmentioning
confidence: 99%
“…Despite a decrease in anti-termination activity upon introduction of heterologous interactions, presumably due to the loss of the interaction between the NusA protein and the boxB/N complex, the two-plasmid system has been shown to be a sensitive method for the analysis of small changes in binding affinity of RNA-polypeptide interactions. This bacterial system has also been shown to be a powerful tool in the screening and selection of novel RNA-binding peptides targeting the HIV Revresponse element (RRE) from combinatorial libraries (Harada et al, 1996;Peled-Zehavi et al, 2003;Sugaya et al, 2008a), as well as for the selection of novel peptide-binding RNAs (Iwazaki et al, 2005;Sugaya et al, 2008b). However, there appeared to be limitations on the size of RNAs that can be accommodated in the antitermination complex, with only the interaction of relatively small RNA stem-loops with their cognate polypeptides being detected using the two-plasmid system.…”
Section: Introductionmentioning
confidence: 99%